Denis Lambin versus Joachim Périon : quel style pour traduire Aristote ? - Laurence Bernard-Pradelle (Astérion)
This paper proposes a reflexion on why did scholars continue to traslate Greek into Latin all the sixteenth century long, and how they justifed their works. For example in 1540, J. Perion began a new translation of Aristotle to answer to the needs of a readership who certainly knew Latin better than Greek. Founded on Bruni’s ideas on translation, he used Cicero's style because he thought it was the most appropriate to Greek philosophy, as Cicero already translated it into Latin. So did Denis Lambin thirty years later, when he proposed a new translation of his own, without calling into question the choice of the language, that it to say without questionning what language, either latin or vernacular, would be more efficient. He justified his project by the difficulty of the exercise of translation itself, and by the fact that he was the only scholar able to perfectly achieve it.